MENGHITUNG TINGKAT PRODUKTIVITAS TOTAL DALAM UPAYA MENINGKATKAN DAYA SAING PERUSAHAAN - Parwati, Indri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
Tourism is a kind sector that can make increase of devisa and promotion to other country. A support factor for tourism to enjoy their facation is hotel’s industry. TRIM III Hotel need to do productivity calculating as base planning to increasing productivity in future. To calculating productivity in TRIM III Hotel using OMAX method, Marvin E. Mundhel, and Kendrick and D. Creamer. Based on calculating result by OMAX method gotten the higgest attainment indicator value at March 2005 equal to 737,71 % with increase to early period equal to 145,90 % and experiencing increase of productivity to previous period equal to 50,14 %, while the lowest attainment indicator at October 2004 equal to 227,05 % with decrease of productivity to previous period equal to 24,32 % and experiencing decrease of productivity to previous period equal to 55,57 %. By use Marvin E. Mundhel method the higgest productivity index’s value at April 2004 equal to 109,16 % with increase of productivity equal to 9,75% to previous period and the lowest productivity index value at October 2005 equal to 72,34 % with decrease of productivity equal to 13,14 % to previous period. Kendrick and D. Creamer method the higgest productivity index’s value at April 2004 equal to 154,88 % with increase of productivity equal to 18,35 % to previous period and the lowest productivity index’s value at October 2005 equal to 106,45 % with decrease of productivity equal to 22,81 to previous period.